2015
DOI: 10.1155/2015/862391
|View full text |Cite
|
Sign up to set email alerts
|

Flax Fiber Hydrophobic Extract Inhibits Human Skin Cells Inflammation and Causes Remodeling of Extracellular Matrix and Wound Closure Activation

Abstract: Inflammation is the basis of many diseases, with chronic wounds amongst them, limiting cell proliferation and tissue regeneration. Our previous preclinical study of flax fiber applied as a wound dressing and analysis of its components impact on the fibroblast transcriptome suggested flax fiber hydrophobic extract use as an anti-inflammatory and wound healing preparation. The extract contains cannabidiol (CBD), phytosterols, and unsaturated fatty acids, showing great promise in wound healing. In in vitro prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Prolonged inflammation inhibits the proliferation and differentiation of epithelial cells due to reactive oxygen species production (Kasuya & Tokura, ). Moreover, wounds that take longer to heal cause more pain and are susceptible to infection (Styrczewska et al, ). CBD effects on inflammation have already been described using both in vivo and in vitro models of chronic and acute diseases (Burstein, ; Pisanti et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged inflammation inhibits the proliferation and differentiation of epithelial cells due to reactive oxygen species production (Kasuya & Tokura, ). Moreover, wounds that take longer to heal cause more pain and are susceptible to infection (Styrczewska et al, ). CBD effects on inflammation have already been described using both in vivo and in vitro models of chronic and acute diseases (Burstein, ; Pisanti et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Styrczewska et al developed a wound dressing composed of flax fiber containing CBD and concluded that this resource showed promising results in healing and activating cell proliferation and migration in vitro. CBD did not alter the morphology or proliferation of fibroblasts and keratinocytes and was also responsible for exerting an antiinflammatory effect and increased the activity of matrix metalloproteinases (Styrczewska et al, ). Thus, the influence of CBD on keratinocytes is still controversial, and further studies are needed to investigate its effects and identify the exact mechanisms of action.…”
Section: Resultsmentioning
confidence: 99%
“…Real-time PCR showed inhibition of proinflammatory gene expression in skin fibroblasts, in-cluding interleukins 1β and 6, cyclooxygenase 2, and activation of the expression of suppressor of cytokine and chemokine signaling 1, which is a known antiinflammatory gene. The altered expression of other genes showed a similar direction of extract activity, lowering migration, and adhesion of leukocytes (MCP1 and ICAM1), and these changes were correlated with the cannabidiol concentration in the extract [149].…”
Section: Plant-derived Extractsmentioning
confidence: 78%
“…There are biological endocannabinoids (produced by human cells, e.g., anandamide or plant-derived terpenophenolics) and synthetic cannabinoids (e.g., HU-243, WIN-55,212-2). Reports show the important role of terpenophenol as an agent with analgesic and anti-inflammatory properties [ 24 , 25 ]. Preclinical studies have demonstrated the antioxidant, anti-inflammatory, antiviral, and vasodilating properties of linseed dressings.…”
Section: Discussionmentioning
confidence: 99%